Error Analysis of Misspelled Word in Outdoor Commercial Advertising in Surabaya - Fikri, Muhammad Haidar (Language Horizon: Journal of Language Studies, 2022)
Error Analysis of Misspelled Word in Outdoor Commercial Advertising in Surabaya Haidar Fikri English Literature, Faculty of Language and Arts, Universitas Negeri Surabaya m.fikri2@mhs.unesa.ac.id Abstract Advertising is the media that has the power to convey any message. The use of English inappropriately makes their message unclear and fails to be perceived by people as readers. This study tries to find out the error levels of words in advertisements seen from Carl James (1998). The research was conducted in Lidah Wetan, Surabaya. Descriptive qualitative was employed as the approach in this study. This study was carried out by collecting outdoor commercial advertisements. The fifteen advertisements were analyzed and classified into four types of errors. The results revealed that dyslexic and confusibles errors were the two most common types of error levels in outdoor commercial advertisements. The interference of the Indonesian language is the major cause of misspelled words. The copywriters should understand the English grammar and vocabulary before they create the message on the board in English to avoid misspelling that may cause readers misunderstand the intended messages. Keywords: language error, misspelled word, outdoor advertisements